THE UTILIZATION OF PROJECT MANAGEMENT TECHNIQUES IN THE CONSTRUCTION OF PYRAMIDS IN EGYPT WITH SPECIAL REFERENCE TO THE GREAT PYRAMID IN GIZA - Ngeno, Joseph Kipruto (IJRDO - Journal of Business Management, 2022)
This paper examines the evolution of pyramid construction in Egypt from a project management perspective. The study is based on desktop research and literature review. Its purpose is to examine the extent to which project management techniques were utilized during the construction of the pyramids. And while it is true that the pyramids were built some 4,500 years ago, it is equally the techniques used are valid now as they were then. A project management model developed by Goodman & Love (1980) as an analytical framework in this study. Results show that the construction met all the requirements of the model. The concepts of time, cost and specification were applied.  The innovations adopted, challenges faced and how they were overcome were also explored.  During the study it was found that the latest research indicate that the pyramids were built by the Egyptians themselves as opposed to slaves.  Leading authorities in this area including Salima Ikram, Zawi Hawas, Wideman and others have published extensively on this subject and have provided irrefutable documentary evidence to support this view. These findings, provide a new dimension in the manner in which the workforce was recruited, organized and paid. This is a major consideration in project management. It is therefore important that as new information is obtained, its implications are examined. Finally, the literature review examined the latest developments in project management thereby contributing to the growing body of knowledge in this field. The study will also serve as current reference material for students and researchers in project management and projects in antiquity.